Divergent Leakage Features of Anticyclonic and Cyclonic Mesoscale Eddies - Yanjiang Lin; Guihua Wang (Geophysical Research Letters)
Abstract Eddies can carry water over hundreds of kilometers, but there is also water leakage during eddy movement. By tracking the global drifters' trajectories related to oceanic eddies, we find that, in the Northern (Southern) Hemisphere, drifters in the eddies tend to leave anticyclonic/cyclonic eddies from the rear left/right (right/left) side relative to the eddy movement direction. A further simulation displays that there are potential vorticity (PV) channel structures in eddies' margins, and particles tend to leave the eddies via the channel. Theoretical analyses illustrate that particles on the PV channel always propagate oppositely to the eddy rotation due to the relative vorticity gradient of eddy flow. This study offers a new perspective on eddies' leakage and may be crucial for investigating oceanic mass redistribution.